Comics and the Demystification of France's Immigration 'Problem': Reading Christophe Dabitch's Immigrants. (2nd January 2016) - Howell, Jennifer
Abstract : While universalism constitutes the foundation of French republicanism, public discourse and changes in immigration law have revealed that racial and/or ethnic discrimination and exclusion are necessary for cultural assimilation and for the protection of France's 'universalist' model. Studies have also shown that at least 40% of the French population is of foreign origin. So how has France justified the reconciliation of universalism and particularism (now referred to as communitarianism) in certain instances but not others? Christophe Dabitch's collaborative comic-book project, Immigrants (2010), aims to deconstruct the French republican narrative of universalism by using a popular medium that is both transcultural and transnational. An effective collage of visual styles, reproduced testimony and scholarship on immigration in France, Dabitch's album proposes writing an alternative French history of immigration and invites readers to question founding mythologies which have erected France as the country of human rights. This article has three objectives: to present Immigrants as a serious historical and artistic project on immigration; to critically examine this publication's purpose (can comics effectively demonstrate that immigration is a common but significant aspect of nation building?); and to explore how comics can positively re-imagine France as a métropole cosmopolite, as an international point of convergence.